Incidence of type 1 and type 2 diabetes, between 2012-2016, among children and adolescents in Qatar - Alyafei, Fawzia; Soliman, Ashraf; Alkhalaf, Fawziya; Sabt, Aml; De Sanctis, Vincenzo; Waseef, Reem; Elsayed, Nagwa (Acta Biomedica Atenei Parmensis, 2018)
Introduction: Diagnoses of type 1 DM (T1DM) and type 2 diabetes mellitus (T2DM) in youths present a substantial clinical and public health burden. The aim of this study was to determine the incidence and trend of T1DM and T2DM, among children aged 0–14 years, in Qatar. Methods: This prospective cohort study was performed to ascertain all new cases of T1DM and T2DM 2 in Qatar as per the registry of the National Paediatric Diabetes Centre (the only tertiary care center treating children with DM in Qatar. Age-standardized and age-specific annual incidence rates for age groups 0.5-14 years were calculated. Results: A total of 440 youths with T1DM (0.5 to 14 years of age) and 45 with T2DM (5 to 14 years of age) were identified in Qatar. The inclusive unadjusted estimated incidence rates of T1DM in this population over the period between 2012-2016 was 28.39/100,000 with a 95% CI of 31.82-40.03. This was significantly higher compared to the unadjusted estimated incidence registered between 2006-2011 (23.15/100,000). No case of T2DM were registered before 2008. In the following years the incidence of T2DM increased from 1.82 per 100,000 in 2012 to 2.7 per 100,000 in 2016, with an incidence of T2DM equal to 2.9/100,000 per year. Conclusions: A relatively higher incidence of T1DM compared to incidence reported worldwide have been documented in Qatar. The incidence rate increased in the period 2012-2016 compared to 2006-2011. Further studies are required to determine the causes of these increases.